2017
DOI: 10.1111/jpi.12431
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin protects against maternal obesity‐associated oxidative stress and meiotic defects in oocytes via the SIRT3‐SOD2‐dependent pathway

Abstract: Maternal obesity in humans is associated with poor outcomes across the reproductive spectrum. Emerging evidence indicates that these defects are likely attributed to factors within the oocyte. Although various molecules and pathways may contribute to impaired oocyte quality, prevention of fertility issues associated with maternal obesity is a challenge. Using mice fed a high-fat diet (HFD) as an obesity model, we document spindle disorganization, chromosome misalignment, and elevated reactive oxygen species (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
135
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(150 citation statements)
references
References 63 publications
13
135
0
2
Order By: Relevance
“…For example, previous studies reported in the rat that intraperitoneal injection of 15 mg/kg MT reduced gastrointestinal motility disorder caused by noise stress, while intraperitoneal injection of 40 mg/kg MT attenuated effectively methotrexate‐induced oxidative stress and small intestinal damage . Oral administration of 30 mg/kg MT to mice fed a high‐fat diet for three consecutive weeks can resist obesity . In addition, rats were given to intraperitoneal injection of MT at a dose of 15 mg/kg/day (body weight) between 7:00 and 8:00 to explore the role of MT in ameliorating cognitive impairment induced by SD .…”
Section: Discussionmentioning
confidence: 80%
“…For example, previous studies reported in the rat that intraperitoneal injection of 15 mg/kg MT reduced gastrointestinal motility disorder caused by noise stress, while intraperitoneal injection of 40 mg/kg MT attenuated effectively methotrexate‐induced oxidative stress and small intestinal damage . Oral administration of 30 mg/kg MT to mice fed a high‐fat diet for three consecutive weeks can resist obesity . In addition, rats were given to intraperitoneal injection of MT at a dose of 15 mg/kg/day (body weight) between 7:00 and 8:00 to explore the role of MT in ameliorating cognitive impairment induced by SD .…”
Section: Discussionmentioning
confidence: 80%
“…Because of the worldwide increase in obesity, female fertility has shown a marked decline. Since mitochondrial SIRT3 is suppressed in obese rodents, which leads to reduced SOD2 and unrestrained ROS formation, Han et al [210] fed melatonin to obese rats. As anticipated, melatonin greatly improved oocyte quality and fertilizability; this was accompanied by an activation (deacetylation) of SIRT3, which induced SOD2 ultimately reducing oxidative stress in the oocytes.…”
Section: The Melatonin/sirt3 Interactionsmentioning
confidence: 99%
“…This suggests that the antioxidant action of melatonin in oocytes depends on stimulation (deacetylation) of SIRT3 which enhances the activity of the antioxidant enzyme, superoxide dismutase. Figure drawn from the data of Han et al [210]. * p > 0.001.…”
Section: Figurementioning
confidence: 99%
“…20 In brief, female ICR mice were primed with pregnant mare serum gonadotropin. 20 In brief, female ICR mice were primed with pregnant mare serum gonadotropin.…”
Section: In Vitro Fertilization and Embryo Culturementioning
confidence: 99%